PENDIDIKAN KARAKTER DALAM TARI MANDUDA PADA MASYARAKAT SIMALUNGUN - Sylvia Purnama Sari (Universitas Negeri Medan, 2017)
This study aimed to describe Character Education In Dance Manduda the Community Simalungun. The research was conducted in June until the month of August 2016, this study uses theories that relate to topics such as the theory of education and character, understanding the value of character education, the meaning and understanding of dance movement Manduda. This study uses a qualitative method. The object of this research is Manduda dance.Data were obtained by the researchers themselves as a research instrument by using observation, interview, and documentation. Data were analyzed using qualitative descriptive analysis to describe the state of the object in the field. The location of this research was conducted in District Pematang Raya.The results showed Manduda dance is a dance that describes the excitement and joy in harvest rice Simalungun society. Dance education Manduda contains characters that include the value religus, honesty, tolerance, discipline, hard work, creative, independent, democratic, national spirit, patriotism, friendship / communicative, peace-loving, caring environment, social care and responsibility.